2018
DOI: 10.1088/1361-648x/aac61d
|View full text |Cite
|
Sign up to set email alerts
|

Strong antisymmetric spin–orbit coupling and superconducting properties: the case of noncentrosymmetric LaPtSi

Abstract: In this work we aim to analyze the effect of a strong antisymmetric spin-orbit coupling (ASOC) on the superconductivity of noncentrosymmetric LaPtSi. We study the energy gap structure of polycrystalline LaPtSi by using magnetic penetration depth measurements down to 0.02T . We observed a dirty s-wave behavior, which provides compelling evidence that the spin-singlet component of the mixed pairing state is highly dominant. This is consistent with previous results in the sense that the mere presence of a strong … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…From the observed splitting, the value of the spin-orbit coupling for a chosen momentum can be evaluated. These compounds are characterized by the relatively large value of the spin-orbit coupling (around 0.5 eV) in relation to the other compounds of this class [22]. The existence of such a strong spin-orbit coupling can induce effectively a mixing of the singlet and triplet superconducting pairing [4,35,36].…”
Section: Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the observed splitting, the value of the spin-orbit coupling for a chosen momentum can be evaluated. These compounds are characterized by the relatively large value of the spin-orbit coupling (around 0.5 eV) in relation to the other compounds of this class [22]. The existence of such a strong spin-orbit coupling can induce effectively a mixing of the singlet and triplet superconducting pairing [4,35,36].…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…The compounds from the ThTSi family (where T = Co, Ir, Ni, and Pt) crystallize with a non-centrosymmetric tetragonal structure of the LaPtSi-type (space group I4 1 md, No. 109) [19][20][21][22] (see Fig. 1).…”
Section: Introductionmentioning
confidence: 98%
“…Among them, spatial inversion symmetry has drawn considerable interest in condensed matter physics, since its breaking gives rise to fascinating physical phenomena, such as a spontaneous electric polarization and nonreciprocal transport [1][2][3][4][5]. The breaking of spatial inversion symmetry also leads to an antisymmetric spin polarization in terms of the wave vectors in electronic band structures, which has been often found in the noncentrosymmetric crystals with the strong relativistic spin-orbit coupling [6][7][8], such as polar crystals with the Rashba-type spin-orbit coupling [9][10][11][12], chiral crystals with the Weyl-type spin-orbit coupling [13,14], and other noncentrosymmetric crystals with the Isingtype spin-orbit coupling [15][16][17][18]. The antisymmetric spin polarization becomes a source of spin-related parityviolating physical phenomena [19][20][21][22], such as the spin Hall effect [23][24][25][26][27] and the Edelstein effect [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in non-centrosymmetric heavy-fermion superconductors it was found that broken inversion symmetry is not the only requirement for unconventional superconductivity [14]. Rather the 4f electrons must actually play a crucial role since all unconventional superconducting properties have not been observed in their La analogues [15,16].…”
Section: Introductionmentioning
confidence: 99%